Local Government Crisis Communication Strategy: Case Study of Demands for Arrears in Employee Income Additional Payments - M. Amin; Mujahid Mujahid; Nur Alim Djalil (Newinera Publisher, 2024)
In handling the crisis, the Regional Government of Penajam Paser Utara Regency carried out crisis identification first, carried out rapid research into the phenomena that occurred by observing the situation so that crisis management was right on target. Crisis analysis is also carried out, namely the regional government analyzes the data that has been collected to take strategic steps. The crisis communication strategies applied in this crisis case are 1) Diminish strategies, namely by means of justification and excuse strategies, 2) Rebuild strategies, namely by means of compensation, apology, and 3) Reinforcing / Bolstering strategies, namely by means of victimage. There are several factors inhibiting the implementation of crisis communication, including a lack of transparency or openness towards communication carried out by the Regional Government. Researchers recommend forming a team to handle the crisis that occurred. As well as the Regional Government to be more active in communicating or having direct contact with ASN, especially those at staff level.